Modeling C9orf72-Related Frontotemporal Dementia and Amyotrophic Lateral Sclerosis in Drosophila - Sharpe, Joanne L.; Harper, Nikki S.; Garner, Duncan R.; West, Ryan J. H. (Frontiers in Cellular Neuroscience, 2021)
An intronic hexanucleotide (GGGGCC) expansion in the C9orf72 gene is the most common genetic cause of frontotemporal dementia and amyotrophic lateral sclerosis. In the decade following its discovery, much progress has been made in enhancing our understanding of how it precipitates disease. Both loss of function caused by reduced C9orf72 transcript levels, and gain of function mechanisms, triggered by the production of repetitive sense and antisense RNA and dipeptide repeat proteins, are thought to contribute to the toxicity. Drosophila models, with their unrivalled genetic tractability and short lifespan, have played a key role in developing our understanding of C9orf72-related FTD/ALS. There is no C9orf72 homologue in fly, and although this precludes investigations into loss of function toxicity, it is useful for elucidating mechanisms underpinning gain of function toxicity. To date there are a range of Drosophila C9orf72 models, encompassing different aspects of gain of function toxicity. In addition to pure repeat transgenes, which produce both repeat RNA and dipeptide repeat proteins (DPRs), RNA only models and DPR models have been generated to unpick the individual contributions of RNA and each dipeptide repeat protein to C9orf72 toxicity. In this review, we discuss how Drosophila models have shaped our understanding of C9orf72 gain of function toxicity, and address opportunities to utilise these models for further research.